Stakeholders’ Perceptions on the Provision and Management of Personnel Services in North Central StatesColleges of Education, Nigeria. - Ojibara, N. B. L.; Maina, B. A. (International Journal of Educational Management, 2022)
This study examined the stakeholders’ perceptions on the provision and management of personnel services in North Central States Colleges of Education, Nigeria. The purpose of the study was to ascertain the adequacy of recreational, transport and health/clinic facilities and to assess their level of management and maintenance. Three Colleges of Education from North Central State of Nigeria were used as sample for the study, while the simple random sampling technique was employed in drawing 388 stakeholders made up of students, service staff and top management staff in the Colleges as respondents for the study. Three research questions were raised to guide the study, while a self-designed questionnaire was administered on the respondents. Frequency count and percentages were used in analyzing the collected data. Some of the findings of the study revealed that transport services were available but not free in the Colleges. Based on the findings, it was recommended, among others, that adequate fund should be allocated to the Colleges of Education in Nigeria by the federal and state governments to take care of the personnel needs. Also, the college management should ensure that personnel demands are satisfied in order to maintain free, peaceful, and conducive teaching/learning environment.